Halal beauty supply chain and sustainable operational excellence: A moderator of the post-SARS-CoV-2 mitigation strategy - Fernando, Yudi; Mergeresa, Fineke; Ika Sari, Wahyuni-TD; Nurul Sabrina, Hazarasim (Emerald Publisher, 2024)
Purpose: The purpose of this study is twofold. The first objective is to examine the impact of the halal beauty supply chain (HBSC) on sustainable operational excellence (SOE). The second objective is to investigate Post-SARS-CoV-2 mitigation strategies executed by halal beauty companies in Malaysia. Design/methodology/approach: The questionnaire was distributed via an online survey, and data were analyzed from 143 beauty firms and their supply chains. This study used a structural equation modeling technique to test the validity of the research model and hypotheses. Findings: This study found that halal transportation, halal manufacturing, halal packaging and post-SARS-CoV-2 mitigation strategies had a significant and direct effect on SOE. The halal procurement was the only predictor that affected the SOE when the post-SARS-CoV-2 mitigation strategy was computed as a moderator in the research model. Practical implications: Consumers have the right to determine what is a good product by researching it before purchase and consumption. Muslim customers must pay attention and seek information on how the product is manufactured and distributed using sustainable materials according to Shariah law. This is because consumers are responsible for both themselves and others. Companies must view consumer awareness of product qualities as a business opportunity. Halal beauty companies should frequently execute risk mapping and mitigation strategies to decrease risk, improve revenues and attain sustainable business objectives. Originality/value: Although the HBSC encompasses numerous complicated areas, such as strategic marketing, operations, as well as behavioral and Shariah compliance, there is a deficiency of literature on how firms mitigate risk in the halal supply chain. This study proposes a framework for a HBSC that achieves and leverages SOE.